Intersectionality and complexity in the representation of 'queer' sexualities and genders in African women's short fiction - Du Preez, Jenny BoÅºena (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2019)
This thesis sets out to contribute to the growing body of knowledge about queer sexualities and genders in Africa by examining their depiction in selected post-2000 African women's short fiction written in English. Post-2000, the short story form has become the primary vehicle for queer representations by African women writers, and is thus an important development in the burgeoning body of queer literature by African writers. Broadly speaking, this literary formation can be defined as anti-homophobic, feminist and politically pragmatic. Using an intersectional lens, this thesis sets out to examine four significant strands in the political work these stories engage in. The chapters are structured around four main points of contention that have particular significance at the intersection of 'queer', 'women' and 'Africa'. Firstly, I examine South African short stories that perform what I call queer conversations with history: imaginatively asserting a queer South African history, writing back against a male-dominated and heterosexist literary canon and, in doing so, contributing to the reimagination of the contemporary South African nation. Secondly, I analyse short stories from Africa that foreground the family, both as social formation and ideology. I examine how these stories 'fracture' this powerful and naturalised heterosexist concept by depicting the tensions and contradictions that queer characters experience in relation to family. Thirdly, I consider short stories from various African contexts that work to reconceptualise queer sexuality in relation to religious discourse in order to challenge homophobic and patriarchal religious authority. Finally, I examine queer, feminist erotic short stories by African women writers that challenges various colonialist, racist, sexist and lesbophobic discourses that have historically stifled the portrayal of sex and erotic experience between women.
Keywords: Sexual minority culture; Sexual minorities' writings; African fiction -- Women authors -- History and criticism; Gender identity in literature; Short stories, South African; Feminism in literature; Political poetry; Eroticism in literature; Lesbianism in literature